2006
DOI: 10.1590/s0103-50532006000700014
|View full text |Cite
|
Sign up to set email alerts
|

New heterogeneous metal-oxides based catalyst for vegetable oil trans-esterification

Abstract: Neste trabalho são apresentados a preparação de novos materiais obtidos da co-precipitação de alumina e óxidos de estanho e zinco e seu uso como sistemas catalíticos ativos para alcoólise de óleos vegetais. Foi observado que estes óxidos metálicos do tipo (Al 2 O 3 ) X (SnO) Y (ZnO) Z são ativos para a alcoólise do óleo de soja usando diversos álcoois, incluindo ramificados. Os melhores resultados foram observados utilizando metanol, sendo atingidas conversões acima de 80% em 4 horas. Foi também possível recic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 20 publications
0
44
0
4
Order By: Relevance
“…As result, catalysts based on metal salts such as aluminium, titanium and tin halides are widely used in several synthetic methods [17]. Conversely, the use of catalysts based on metal complexes as such rare earth metal triflates and metallocene compounds has been also developed [18]. Recently, the use of both types of catalysts, i.e.…”
Section: Environmental Benefits Of Use Of Lewis Acid Catalysts For Bimentioning
confidence: 99%
“…As result, catalysts based on metal salts such as aluminium, titanium and tin halides are widely used in several synthetic methods [17]. Conversely, the use of catalysts based on metal complexes as such rare earth metal triflates and metallocene compounds has been also developed [18]. Recently, the use of both types of catalysts, i.e.…”
Section: Environmental Benefits Of Use Of Lewis Acid Catalysts For Bimentioning
confidence: 99%
“…The resulting mixture was kneaded thoroughly and aged for 2 hrs at 23 °C, followed by drying at 23 °C for 12 hrs. After drying, 4.5 mL of a sodium hydroxide solution (2.0 M) was added to the dried solid according to the method used in reference [22] . The mixture was again kneaded and thereafter aged for 2 hrs at 23 °C and dried at 23 °C for 12 hrs.…”
Section: Metal Oxide Catalyst Preparationmentioning
confidence: 99%
“…Several studies reported that Mg-Al hydrotalcites [4,5,21] and metal oxides (Al2O3-SnO, Al2O3-ZnO) [22] were active for the transesterification of vegetable oils with methanol at a relatively low reaction temperature. Although sodium hydroxide or sodium carbonate compounds were used in these catalyst preparations, the catalytic activity and deactivation behavior of the metal oxide catalysts were reported as originating from metal oxides (Al2O3-SnO, Al2O3-ZnO) or Mg-Al hydrotalcites sites [4,5,21,22]. As a result, there are conflicting reports of the catalytic activity of the metal oxides catalysts at low temperature for transesterification of vegetable oil and methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Transesterification is a widespread process used for obtaining biodiesel and involves the catalyzed reaction of triacylglycerides (TAGs) and short-chain mono-alcohols (such as methanol and ethanol) to produce fatty acid methyl or ethyl esters (biodiesel). 3,4 This process was the chosen technology by several biofuel programs, such as the National Program of Production and Use of Biodiesel (PNPB) in Brazil. 2 Biodiesel is considered the best fuel substitute for diesel due to its physical properties, which are close to those of fossil diesel.…”
Section: Introductionmentioning
confidence: 99%